(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es ((3GdMSf Hf Ydjs)
(3ChdgG (B:s
(3ChdgG(B: (3Gdbhd aj GdWhGa, hajg KdGKI ebGUO GdChd aj GdebOeGJ hgj hGLHI hefOhHI, aGdhGLHGJ(B: (3GdWgGQI ef GdMOK GdCUZQ hGdCcHQ aj GdWhGa GdhGLH HdG NdGas
(3BNQgG (B:s
(3BNQgG(B: (3aj YOe GdhLhH ajgG hbO eQ GdcdGe ajg eaUdG hEf cGf GdeQGO ef GdhLhH HGdfSHI Edi GdUHj GdKHhJ dYOe GdJcdja Ydjg ajeJfY ef eHGTQI GdfSGA hdh HYO GdHdhZ MJi jCJj HWhGagf ceG JeJfY GdUHjI hGdfSGA Yf GdQLGd MJi jWaf ceG LeYJ GdcdGe aj Pdc ajeG eVis
(3GdfSNI ebGHdI Ydi eShOI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis